Kehidupan Tokoh Fukiko SebagaiSingle MotherDi Pulau Sae Yang Tercermin Pada Novel Shima Wa Bokura To Karya Mizuki Tsujimura - Kurnia Sari, Ni Wayan Intan; Ari Sulatri, Ni Luh Putu; Luhur Wedayanti, Ni Putu (Humanis, 2019)
The title of this paper is "The Life of Fukiko As Single Mother in Sae Island that Reflected in a Novel Called Shima Wa Bokura To by Mizuki Tsujimura". The aim of this research is analysis the problems that Fukiko has to face as a single mother and her efforts to resolve these that reflected in a novel called Shima Wa Bokura To by Mizuki Tsujimura.The method used in this research is descriptive analysis. Theories used in this research are literature sociology theory by Damono (2002) and social problem theory by Soekanto (1999).As a result, there are four problems that Fukiko has to face as a single mother; 1) economic problems; 2) difficulty in raising children; 3) rejection by her family and; 4) viewed negatively by society. Fukiko’s efforts as a single mother to resolveproblems that mentioned before; 1) make a creative products to sell; 2)ask her neighbor to help; 3) get out from her family's and start a new life, and; 4) face them with patient and politely.